2018
DOI: 10.1117/1.jbo.23.3.036004
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive assessment of collagen hydrogel cross-linking using time-resolved autofluorescence imaging

Abstract: We investigate the use of a fiber-based, multispectral fluorescence lifetime imaging (FLIm) system to nondestructively monitor changes in mechanical properties of collagen hydrogels caused by controlled application of widely used cross-linking agents, glutaraldehyde (GTA) and ribose. Postcross-linking, fluorescence lifetime images are acquired prior to the hydrogels being processed by rheological or tensile testing to directly probe gel mechanical properties. To preserve the sterility of the ribose-treated gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…A major challenge in the research and translation of tissue‐engineered products is the cost and time associated with destructive testing methods. The inexpensive, fiber‐based interface of the FLIm‐based system can be incorporated into a standard biosafety cabinet for sterile imaging and repeated measurements of samples (Sherlock, et al, ). The ability to continuously monitor tissue quality enables quick adjustments to varying rates of tissue development, the scrapping and restarting of poorly developing tissue, and predictive capabilities of final tissue quality.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge in the research and translation of tissue‐engineered products is the cost and time associated with destructive testing methods. The inexpensive, fiber‐based interface of the FLIm‐based system can be incorporated into a standard biosafety cabinet for sterile imaging and repeated measurements of samples (Sherlock, et al, ). The ability to continuously monitor tissue quality enables quick adjustments to varying rates of tissue development, the scrapping and restarting of poorly developing tissue, and predictive capabilities of final tissue quality.…”
Section: Discussionmentioning
confidence: 99%
“…FLIm is effective at identifying the unique AF signatures of collagen and collagen cross-links, which occur during tissue maturation. 7,8 Collagen expression and content are frequently used as markers for osteogenic differentiation and indicators of tissue maturation. In this study, we observed strong AF signal in the first three of four channels, corresponding to emission wavelengths of 390/18 nm, 435/40 nm, and 510/84 nm for channels 1, 2, and 3 respectively.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%
“…However, in a previous study, we used the FLIm system under aseptic conditions to longitudinally monitor collagen hydrogels over time with consistent results. 7 Continuing efforts seek to adapt the UBM system to operate under aseptic conditions and increase the functionality of this technique. Current acquisition methods require constructs at least 2 mm in height to provide a sufficient volume for data analysis.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%
“…7(Е)), were found to increase by 197% and 182%, respectively, while the deformation of collagen fibrils was reduced by 58% ( Fig. 7(F) The mechanical properties of the collagen hydrogel after incubation in solutions of ribose and glutaraldehyde (GTA), which promote the formation of collagen cross-links, were studied in paper [140] using multispectral fluorescence lifetime imaging (FLIM). In the case of collagen incubation in GTA, in contrast to ribose, correlations were observed between the fluorescence lifetime and the mechanical properties of collagen.…”
Section: Skinmentioning
confidence: 99%
“…The glycation is a result of the interaction between the glucose molecules and the proteins, which leads to the change of protein structure and to the restriction of To study the glycation of proteins, both the samples of tissues and cells from the objects with natural or artificially induced diabetes mellitus (in vivo glycation), as well as the samples that has been glycated under in vitro conditions are used. Studies of in vitro glycation refer, for example, to human placental type IV collagen, performed by fluorescence analysis, as well as by electrophoresis and densitometry [134]; collagen of bovine skin -using multiphoton microscopy [34]; hemoglobin -by optical coherent tomography [135][136][137], refractometry and IR spectroscopy [122], as well as biochemical analysis [138]; albumin -using fluorescence spectroscopy [70], refractometry [122], and terahertz spectroscopy [138]; collagen of the tendon -through biochemical and biomechanical analyzes [139], as well as to collagen hydrogels -using multispectral fluorescence life time imaging (FLIM) [140]; by incubation in ribose [37,134,139,140], glucose [70,122,135,138,141] or fructose [70,141] solutions. All of them show a sufficiently effective glycation of proteins during 10-11 days of incubation, a change in the mechanical properties of tissues due to the formation of collagen cross-links.…”
Section: Glycation and Non-enzymatic Glycation Of Proteinsmentioning
confidence: 99%